Odpowiedzi

2010-01-19T15:56:16+01:00
A)mnozymy przez (-2)
b)mnozymy przez (-2)
c)mnozymy przez (-1/2)
d)mnozymy przez (0,67)
Najlepsza Odpowiedź!
2010-01-19T15:58:31+01:00
A) x+y=-13 | * (-2)
-2x - 2y = 26
b) 3x + y =-5 | * (-2)
-6x - 2y = 10
c) -x + 4y =2 | *(-1/2)
0,5x - 2y = -1
d)
3x - 3y = 1 | *(2/3)
2x -2y = 2/3
2010-01-19T16:02:25+01:00
A) x + y = -13 /× (-2)
-2x-2y = 26

b) 3x + y = - 5 / × (-2)
-6x - 2y = 10

c) -x + 4y = 2 / × (-½)
½x - 2y = -1

d) 3x - 3x =1 wnioskuję że tu jest pomyłka i powinno być

3x- 3y = 1 / × ⅔
2x - 2y = ⅔